2019
DOI: 10.31487/j.scr.2019.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate Treatment in Pseudoxanthoma Elasticum (PXE)-Preventing ReOcclusion After Surgery for Critical Limb Ischaemia

Abstract: Pseudoxanthoma elasticum (PXE) is a rare metabolic disease characterized by reduced plasma pyrophosphate (PPi) concentration, causing progressive soft tissue calcification represented by skin lesions, central vision lost and peripheral artery disease. PXE is currently incurable. Previous reports have shown early high failure after revascularization by unknown mechanism. Reports of oral PPi administration have shown to decrease tissue calcification in a murine model of PXE. We report the outcome of one patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…To reduce the ion load and the amount of sodium in PP i , we first turned to the Na 2 H 2 P 2 O 7 salt form which contains half as much sodium as the previously utilized tetrasodium (Na 4 P 2 O 7 ) variant 22 . A case report has been published describing oral pyrophosphate treatment of a PXE patient utilizing Na 2 H 2 P 2 O 7 dissolved in water 29 . To avoid the unpleasant taste, we used capsulated PP i salts instead of water‐based solution as the form of delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the ion load and the amount of sodium in PP i , we first turned to the Na 2 H 2 P 2 O 7 salt form which contains half as much sodium as the previously utilized tetrasodium (Na 4 P 2 O 7 ) variant 22 . A case report has been published describing oral pyrophosphate treatment of a PXE patient utilizing Na 2 H 2 P 2 O 7 dissolved in water 29 . To avoid the unpleasant taste, we used capsulated PP i salts instead of water‐based solution as the form of delivery.…”
Section: Resultsmentioning
confidence: 99%
“…22 A case report has been published describing oral pyrophosphate treatment of a PXE patient utilizing Na 2 H 2 P 2 O 7 dissolved in water. 29 To avoid the unpleasant taste, we used capsulated PP i salts instead of water-based solution as the form of delivery. Two different capsules were tested: gelatin and HPMCP-type cellulose capsules, which can resist dissolution at the acidic pH of gastric fluid.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…We have learned much about ABCC6 [ 21 ] since its initial discovery 20 years ago [ 5 , 6 , 7 ], from its transcriptional regulation [ 215 , 216 , 217 ], expression profile [ 79 , 81 , 128 ], and molecular function and connections to an existing molecular pathway [ 8 , 9 ], to means and ways to rescue this transporter and treatments for PXE [ 18 , 19 , 92 , 98 , 99 ]. In two decades, PXE has gone from gene discovery to early clinical trials [ 126 , 218 ], a remarkable feat for rare disorders with significant morbidity but low mortality. At the time of this writing, PXE alone has been the subject of more than 2000 peer-reviewed publications (PubMed citations) as well as many other book chapters and reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that oral administration of tetrasodium-PPi inhibited connective tissue mineralization in both Abcc6 −/− and Enpp1 asj mice [ 16 ]. Further modifications, including use of a disodium-PPi, was tested in individuals with PXE, without apparent gastrointestinal side effects, potentially providing a new treatment modality for PXE and related ectopic mineralization disorders [ 71 ]. Based on these studies, a disodium-PPi absorption trial in PXE patients is under way (NCT04441671; last updated 22 June 2020).…”
Section: Therapy Development For Ectopic Mineralization Disordersmentioning
confidence: 99%